PENERAPAN KONSEP SOSIOLOGI OLAHRAGA DALAM KONDUSIFITAS PERTANDINGAN - Lija Lumban Gaol; Jesika Sabrina; Henike Sambai Lusiana; Yanto Ferdinan Lumbantobing; Frans Desmon Ebenezer Pasaribu; Yorin Shevina Sitanggang; Nurkadri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Administration in sporting events is important because it ensures the smooth running and fairness of the event. The sociology of sport is a branch of science that studies the relationship between sport and society, including social behavior, group interactions, and the social values ​​that emerge in sporting activities. A conducive match environment is a crucial factor in creating a safe, orderly, sporting, and comfortable sporting atmosphere for athletes, officials, and spectators. This study aims to examine the application of the sociology of sport concept in maintaining a conducive match environment. The research method used is descriptive qualitative through literature review and observation of sporting events. The results indicate that the application of the values ​​of solidarity, sportsmanship, social control, social communication, and social integration can create a more conducive match environment. Furthermore, the roles of the organizing committee, referees, coaches, athletes, and supporters significantly influence the successful application of the sociology of sport concept in matches. Therefore, the application of the sociology of sport concept can be an important strategy in creating a safe and harmonious match environment.